Idea representation and elaboration in design inspiration and fixation experiments. Issue 1 (3rd April 2018) - Vasconcelos, Luis A.; Neroni, Maria A.; Cardoso, Carlos; Crilly, Nathan
Abstract: Design fixation experiments often report that participants exposed to an example solution generate fewer ideas than those who were not. This reduced 'idea fluency' is generally explained as participants' creativity being constrained by the example they have seen. However, the inclusion of an example also introduces other factors that might affect idea fluency in the experiments. We here offer an additional explanation for these results: participants not exposed to the example tend to generate ideas with little elaboration, while the level of detail in the example encourages a similar level of elaboration among stimulated participants. Because idea elaboration is time consuming, non-stimulated participants record more ideas overall. We investigated this hypothesis by reanalyzing data from three different studies; in two of them we found that non-stimulated participants generated more ideas and more ideas containing only text, whilst stimulated participants generated ideas that were more elaborated. Based on the creativity literature, we provide several explanations for the differences in results found across studies. Our findings and explanations have implications for the interpretation of creativity experiments reported to date and for the design of future studies.